Public Versus Private Water Delivery: A Hedonic Cost Approach - Feigenbaum, Susan; Teeples, Ronald (The Review of Economics and Statistics, 1983)
Automotive News, 1967 Almanac (Detroit: Slocum Publishing Co., 1967). Bucklin, Louis P., Competition and Evolution in the Distributive Trades (Englewood Cliffs, New Jersey: Prentice Hall, 1972). Federal Trade Commission, Annual Line of Business Report, 1974 (Washington: FTC, 1981a) processed. , Annual Line of Business Report, 1975 (Washington: FTC, 1981b) processed. Guth, Louis A., Robert A. Schwartz, and David K. Whitcomb, Use of Buyer Concentration Ratios in Tests of Oligopoly Models, this REVIEW 58 (Nov. 1976), 488-491. Jeifreys, James B., The Distribution of Consumer Goods (New York: Cambridge University Press, 1950). Lilly Digest (Indianapolis: Ely Lilly and Co., 1976). Martin, Stephen, Advertising, Concentration and Profitability: The Simultaneity Problem, BellJournal 10 (Autumn 1979), 639-647. National Petroleum News, Fact Book 1976 (New York: McGraw Hill, 1976). NCR, Expenses in Retail Business (Dayton, Ohio: NCR, undated but about 1966 and about 1976). Strickland, Allyn D., and Leonard W. Weiss, Advertising, Concentration, and Price-Cost Margins, Journal of Political Economy 84 (Oct. 1976), 1109-1123. U.S. Department of Commerce, Bureau of Economic Analysis, The Detailed Input-Output Structure of the U. S. Economy: 1972 Volume 1, The Use and Make of Commodities by Industries (Washington, D.C.: Government Printing Office, 1979). U.S. Treasury Department, Internal Revenue Service, Statistics of Income Source Book, 1972, processed. Ward, T. S., The Distribution of Consumer Goods. Structure and Performance (New York: Cambridge University Press, 1973). Weiss, Leonard W., Geographic Size of Markets in Manufacturing, this REVIEW 54 (Aug. 1972), 245-257. , Case Studies in American Industry (New York: John Wiley and Sons, 1980).